2007
DOI: 10.1111/j.1399-3038.2007.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine and circadian aspects (melatonin and β‐endorphin) of atopic dermatitis in the child

Abstract: Atopic dermatitis (AD) is a disease of increasing incidence among paediatric patients. Among the factors involved in its pathogenesis is the alteration of the immune response, and so the objective of this study was to evaluate the involvement of certain neuroendocrine factors with immune properties in the development of the disease. Fifty-five subjects were selected and divided into the following three groups: healthy subjects, those diagnosed with symptomatic AD and those with asymptomatic AD. Plasma levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
(53 reference statements)
0
26
0
Order By: Relevance
“…Contrary to our results, a reduced morning serum melatonin level has been reported in AD. 38 However, previous studies have primarily measured serum melatonin levels in patients with AD, 13,38 but melatonin is secreted with a circadian rhythm in which serum levels peak between midnight and 3 AM, while the daytime levels are low. 39 This makes it difficult to make comparisons or draw conclusions from a serum sample at a single time point.…”
Section: Figurementioning
confidence: 99%
“…Contrary to our results, a reduced morning serum melatonin level has been reported in AD. 38 However, previous studies have primarily measured serum melatonin levels in patients with AD, 13,38 but melatonin is secreted with a circadian rhythm in which serum levels peak between midnight and 3 AM, while the daytime levels are low. 39 This makes it difficult to make comparisons or draw conclusions from a serum sample at a single time point.…”
Section: Figurementioning
confidence: 99%
“…In their studies, they measured the serum IgE and found that it is a marker in atopic dermatitis; however, in our study, we found no relationship between serum IgE and AR severity. A pediatric study also observed a reduction in the serum β -endorphin level in patients with atopic dermatitis [21]. Investigations into lower airway allergic diseases, such as asthma and chronic obstructive pulmonary disease, have demonstrated that the β -endorphin response has been shown to decrease the activation of respiratory muscles and change the pattern of breathing to a more rapid and shallow one [22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover Muñoz-Hoyos et al demonstrated that in the phases of AD outbreaks, patients presented a diurnal reduction in the serum levels of melatonin and β-endorphin, although nocturnal levels were greater for both hormones. They hypothesized that the physiological nocturnal peak of melatonin due to pineal gland production might balance the possible decline of melatonin of extrapineal (immunological or cutaneous) origin during episodes of dermatitis outbreaks [56]. …”
Section: Melatonin and Atopic Eczemamentioning
confidence: 99%